The economy of well-being Creating opportunities for people's well-being and economic growth - Llena-Nozal, Ana (OECD Statistics Working Papers, 2019)
As well-being has matured as a statistical and measurement agenda, it has become increasingly relevant as a "compass" for policy, with a growing number of countries using well-being metrics to guide decision-making and inform budgetary processes. One remaining challenge has consisted in providing policy-makers with a better understanding of the linkages between the drivers of well-being and economic growth. This paper develops the concept of an "Economy of Well-being" as a basis for highlighting these linkages and showing how policy can most effectively leverage them. The paper defines an economy of well-being around the idea of a "virtuous circle" in which individual well-being and long-term economic growth are mutually reinforcing. It also explores the characteristics of an economy of well-being and the conditions under which it can be sustained. Secondly, based on a survey of existing empirical evidence, the paper contributes to outline how economies of well-being can be built. It provides analysis of several important channels through which economic growth and well-being support and reinforce one another, focusing on the multidimensional impact of policies in four areas that research has shown to be important for well-being: Education and Skills; Health; Social Protection and Redistribution; and Gender Equality